Pet psychic - Phillips, Ruby Ann; Isik, Sernur (North Mankato, Minnesota Picture Window Books, 2015)
After her best friend Claire adopts a beagle puppy, Krystal discovers that she can hear and understand animals--a power that comes in handy when she accidentally loses her friend's dog
A gift from book Africa
Scientific Fictions
1 2 13
NEW_ZTN_GN
Keywords: Beagle (Dog breed) -- Juvenile fiction; Human-animal communication -- Juvenile fiction